Sob a espada de Dâmocles: a prática de psicólogas em oncologia pediátrica no Município de Recife-PE - Morais, Sílvia Raquel Santos de (2011)
The overall objective of this research was to understand the practice of psychologists in Pediatric Oncology (OP) in Recife-PE. The specific objectives were to map and thematize the role of these professionals, describe what they are and how are their conceptions of care and understand the implications of these concepts to the everyday know-how. It started from the perspective of existential phenomenology, and more specifically, the Hermeneutic Ontology of Martin Heidegger. The methodology was qualitative, phenomenological inspiration. Collaborated with this study nine psychologists specialized institutions. Data collection relied on interviews, focus groups, dialogues and records in a field diary. These were narratives were transcribed and interpreted by literalized Analytical Sense (Critelli, 2007). The results suggested the presence of five thematic dewatchmen sense of this practice: 1) Time, proximity and intensity: Dimensions of psychological practice in OP, 2) By way of everyday experience: caring in action in the OP, 3) Be- with: the collective work OP, 4) Openness to transcendence as psychological practice in support of OP and 5) Training on the scene: psychologists drifting? Since care was conceived as a set of attitudes / actions / positions opposite the maintenance of life, or in anticipation of liberation, which is sustained by perplexity and emotional availability to children, families and healthcare staff. The implications were expressed in terms of serenity, acceptance and adoption of certain coping strategies that pass through the ontic and ontological dimensions. The imminence of death, the suffering of children and the effects of cancer treatment is called the collaborators to re-draw the very formation and re-create ways by interventional trial everyday and focus on power-is-theother. The results suggest the urgent need for advances in psychology regarding the know-how in health and tertiary care.